2016
DOI: 10.1038/nm.4100
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pre-adapted HIV transmission

Abstract: Human Leukocyte Antigen class I (HLA) restricted CD8+ T lymphocyte (CTL) responses are critical to HIV-1 control. Although HIV can evade these responses, the longer-term impact of viral escape mutants remains unclear, since these variants can also reduce intrinsic viral fitness. To address this question, we here develop a metric to determine the degree of HIV adaptation to an HLA profile. We demonstrate that transmission of viruses pre-adapted to the HLA molecules expressed in the recipient is associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
120
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(138 citation statements)
references
References 109 publications
16
120
2
Order By: Relevance
“…In support of this hypothesis, adaptation to the immune pressure of individual epitopes in the majority of circulating isolates was demonstrated in EBV and HIV . In HIV, a fascinating observation suggested that expression of rare HLA alleles is a selection advantage and associated with lower viral load, presumably because circulating isolates may have adapted to frequent HLA alleles in a population . In HCV, we similarly reported a relatively stable escape mutation in an immunodominant CD8 epitope in NS3 that replaced the immunogenic prototype epitope sequence in the majority of circulating isolates in Europe .…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…In support of this hypothesis, adaptation to the immune pressure of individual epitopes in the majority of circulating isolates was demonstrated in EBV and HIV . In HIV, a fascinating observation suggested that expression of rare HLA alleles is a selection advantage and associated with lower viral load, presumably because circulating isolates may have adapted to frequent HLA alleles in a population . In HCV, we similarly reported a relatively stable escape mutation in an immunodominant CD8 epitope in NS3 that replaced the immunogenic prototype epitope sequence in the majority of circulating isolates in Europe .…”
Section: Introductionsupporting
confidence: 52%
“…22,23 In HIV, a fascinating observation suggested that expression of rare HLA alleles is a selection advantage and associated with lower viral load, presumably because circulating isolates may have adapted to frequent HLA alleles in a population. 24,25 In HCV, we similarly reported a relatively stable escape mutation in an immunodominant CD8 epitope in NS3 that replaced the immunogenic prototype epitope sequence in the majority of circulating isolates in Europe. 19 In a vaccine, such immune targets would likely be less efficient in providing protective immunity, as the relevant antigen is not present in most viral isolates.…”
Section: Introductionmentioning
confidence: 90%
“…The cells were then washed, stained with a 7-AAD staining solution (BD Biosciences) for 30 min at 4°C, and analyzed by flow cytometry. Target cell killing by tumor-specific CD8 T cells was determined using the following formula adapted from previous reports (50,51): Percentage of adjusted tumor cell death = (%7AAD + CD45 − cells with effector T cells – %7AAD + CD45 − cells without effector T cells). Spontaneous cell death was lower than 6 % in all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…However, the latter might also be influenced by demographic differences between the two cohorts. Although certain Gag polymorphisms are known to carry substantial fitness costs, the effect of the transmitted Gag on disease progression ultimately depends on the degree of preadaptation to the recipient's HLA molecules (44)(45)(46). Hence, factors such as the cohort's HLA profile and the age of the epidemic can influence this correlation.…”
Section: Figmentioning
confidence: 99%